2019
DOI: 10.1038/s42005-019-0152-6
|View full text |Cite
|
Sign up to set email alerts
|

Complex networks from classical to quantum

Abstract: NETWORKS IN QUANTUM PHYSICS VS COMPLEXITYNetwork and graph theory fundamentally arises in nearly all aspects of quantum information and computation. As is the case with traditional network science, not arXiv:1702.08459v4 [quant-ph] 16 Apr 2019Box 1 Cross-pollination between the fields of complex networks and quantum information science.In recent years, seminal work has been carried out at the intersection of quantum information and computation and complex network theory. We attempt to catalog the scope of thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
130
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 106 publications
(186 reference statements)
0
130
0
Order By: Relevance
“…Unlike more traditionally studied networks-for instance, social networks or the World Wide Web-the topology and function of networks describing innately physical systems are generally subject to additional constraints that can arise from physical factors. Such factors include the spatial embedding of network elements [44] and the specific physical laws governing the construction and dynamics of and on the networks [45,46]. Thus, accompanying the ongoing use of network science to investigate physical systems, there exists a growing interest in developing physically-motivated network approaches that more explicitly take these constraints and laws into consideration.…”
Section: Network Approaches For Physical Systemsmentioning
confidence: 99%
“…Unlike more traditionally studied networks-for instance, social networks or the World Wide Web-the topology and function of networks describing innately physical systems are generally subject to additional constraints that can arise from physical factors. Such factors include the spatial embedding of network elements [44] and the specific physical laws governing the construction and dynamics of and on the networks [45,46]. Thus, accompanying the ongoing use of network science to investigate physical systems, there exists a growing interest in developing physically-motivated network approaches that more explicitly take these constraints and laws into consideration.…”
Section: Network Approaches For Physical Systemsmentioning
confidence: 99%
“…By character, the combination of network theory and its applications are multidisciplinary and during the recent years a new area applying network theory and complex networks to quantum physical systems has emerged [8,9]. Furthermore, specific features of quantum networks with no classical equivalent have been reported [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The model can be viewed as a unitary construction of a quantum state associated to a graph by the interaction of a walker with the spins (which physically define the graph connectivity). As such, the system generalizes the simple quantum walk [33,34], used in particular to study topological phases in condensed mater [35,36], and quantum states associated to graphs, used for instance, to investigate the graph structure, or more generally, multipartite quantum states as a computational resource [37][38][39][40][41]. We found that, for rather general graphs and a set of simple rules for the motion and interactions, the particlespins system evolves towards a thermal stationary state well described by the eigenvectors of the unitary operator.…”
Section: Introductionmentioning
confidence: 99%